Water Sensitivity Of Warm Porous Asphalt Incorporating Sasobit® - Aman, Mohamad Yusri (2013)
The asphalt industry is making constant efforts to minimize energy consumption and reduce emissions by lowering asphalt production temperature. This can be achieved by incorporating warm asphalt additive named Sasobit®. In this study, rheological properties of a conventional bitumen 60/70 penetration grade with and without Sasobit® at different aging conditions have been investigated. The addition of Sasobit® content increased penetration index and complex modulus (G*), despite reduction in phase angle (δ). By adding 3% Sasobit®, the mixing temperature is decreased from 160°C to 150°C. Meanwhile, adding 1%, 2% and 3% of it increased the PG 70 base binder to PG 73, PG 74 and PG 76, respectively. There was no significant change observed in the mixing temperature from 3% to 4% of Sasobit® addition. However, the reduction of mixing temperatures may prevent moisture from being completely evaporated from the aggregate and so affect the bitumen bond, making the mixture more susceptible to stripping. Two anti-stripping additives, namely hydrated lime and Pavement Modifier (PMD) were used to reduce the destructive effects of moisture. The Dynamic Asphalt Stripping Machine (DASM) that simulate rainfall event was used to enhance stripping. Upon subjected to dynamic stripping, specimens were tested for indirect tensile strength and Cantabro test showed lower strength and less resistance to disintegration due to stripped mastic as compared to immersing condition.